2009
DOI: 10.1097/chi.0b013e3181ae09df
|View full text |Cite
|
Sign up to set email alerts
|

Stable Early Maternal Report of Behavioral Inhibition Predicts Lifetime Social Anxiety Disorder in Adolescence

Abstract: Objective-Behavioral inhibition (BI), a temperamental style identifiable in early childhood, is considered a risk factor for the development of anxiety disorders, particularly social anxiety disorder (SAD). However, few studies examining this question have evaluated the stability of BI across multiple developmental time points and followed participants into adolescence-the developmental period during which risk for SAD onset is at its peak. The current study used a prospective longitudinal design to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
408
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 477 publications
(447 citation statements)
references
References 47 publications
26
408
1
5
Order By: Relevance
“…These results are consistent with previous research demonstrating that BI is associated with increased anxiety in children (Chronis-Tuscano et al, 2009;Schwartz et al, 1999). Importantly, however, these results provide the first evidence that BI may be a related to a range of childhood anxiety disorders rather than just Social Anxiety Disorder, as has been suggested in previous research (Chronis-Tuscano et al, 2009;Muris et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous research demonstrating that BI is associated with increased anxiety in children (Chronis-Tuscano et al, 2009;Schwartz et al, 1999). Importantly, however, these results provide the first evidence that BI may be a related to a range of childhood anxiety disorders rather than just Social Anxiety Disorder, as has been suggested in previous research (Chronis-Tuscano et al, 2009;Muris et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…This was high in comparison to previous research with older samples. 5,12 These rates are, however, consistent with other research with preschool-aged inhibited children. 34 This may be due to the fact that anxiety was assessed at the same time as the participants were selected as being BI.…”
supporting
confidence: 90%
“…3 Several studies have shown that BI is associated with increased risk for anxiety, concurrently and over time. 4,5 The association between BI and anxiety is so strong that there has been some debate regarding the independence of these constructs. 6 As not all BI children develop clinical anxiety, 7 the present research takes a "vulnerability" perspective, which assumes that BI increases risk for anxiety.…”
mentioning
confidence: 99%
See 2 more Smart Citations